Pengaruh ROA, DER, dan EPS Terhadap Return Saham Pada Perusahaan Makanan dan Minuman di ISSI 2019-2022 - Halimatum Munawaroh; Ruliq Suryaningsih (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
Introduction: The research in this thesis is motivated by the results of the financial reports of food and beverage sub-sector companies registered with ISSI for the 2019-2022 period. The selection of this sub-sector is based on the economic conditions of the research period, where this sub-sector is one of Indonesia's economic recoveries and can survive during the pandemic because it is one of society's primary needs. Returns in companies in this subsector experienced fluctuations due to policy changes during the pandemic and a mismatch between theory and the facts that occurred. Research Methods: This type of research is secondary research with a quantitative approach. Data collection uses documentation studies. This study's observations were 208, consisting of 13 sample companies. The sampling technique used is purposive sampling. The analytical method used is panel data regression analysis, which has previously undergone testing stages of the panel data estimation method, panel data regression model selection, classical assumption testing, and significance testing. Results: The results of this research show that the ROA variable has a significant positive effect on stock returns. The DER variable has no significant effect on stock returns. The EPS variable has a significant negative effect on stock returns. The variables ROA, DER, and EPS simultaneously significantly affect stock returns, with the coefficient of determination test results obtaining a value of 0.208. This value explains that the variables ROA, DER, and EPS affect stock returns of 20.8%.